KHẢO SÁT TÍNH CHỊU HẠN CỦA TẬP ĐOÀN LÚA RẪY MIỀN TRUNG VIỆT NAM DỰA VÀO ĐẶC ĐIỂM HÌNH THÁI VÀ PHÂN TÍCH DNA - Ánh, Ông Huỳnh Nguyệt; Tín, Huỳnh Quang; Dũng, Lê Việt (Tạp chí Khoa học Đại học Cần Thơ, 2004)
ABSTRACT A collection of 292 upland rice accessions from the Central of Viet Nam were evaluated of adaptive characteristics to drought by examining the morphological traits and DNA analysis. All upland rice accessions were screened for drought tolerance at seedling stage and were grouped by using 1986 IRRI?s standard. A regression function between soil moisture stress and wilt degree is also studied. Fourty six accessions were taken randomly from these groups and were analysed DNA with eighty primers by Random Amlified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR). Results indicate that the collection were classified as very tolerant (12.32 %), moderately tolerant (39.04 %), moderately susceptible (32.19 %) and susceptible (16.43 %) in drought tolerant ability. Thai Hong, KeKo, Ba Phok accessions showed the best drought tolerant ability. Seven primers OPC06, OPE01, OPL19, OPJ01, OPA09, RTG02 and RTG03 yielded good amplified products. Of which, the primer RTG03 and OPE01 showed more polymorphism than others and can be used to distingguish the test accessions. Keywords: upland rice, drought tolerance, DNA, RAPD-PCR. Title: Studies on drought tolerance of the central Viet nam upland rice collection based on morphological traits and DNA analysis